2019
DOI: 10.1515/tjb-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro apoptotic effect of Zinc(II) complex with N-donor heterocyclic ligand on breast cancer cells

Abstract: Background The synthesis of new ligand and transition metal complexes have drawn great attention in cancer treatment due to excellent DNA cleavage activities and high antitumor activity. Objective The purpose of this study was to synthesize a new Zn(II) complex with 2,2′-bipyridine (bpy) ligand, [Zn(bpy)2(H2O)]2(ClO4), and to investigate the potential therapeutic activity against breast cancer. Materials and methods Zn(II) complex was obtained and structurally characterized using crystallography and other sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Redox inertness potential, low toxicity, excellent biocompatibility, strengthening of the immune system, and increased expression of genes are good reasons for the synthesis of zinc‐based metal complexes. [ 8 ] On the other hand, metal complexes containing phenanthroline ligands and their derivatives could be the future drugs on the market, because they have been shown to be active against various pathological conditions including germs, fungal infections, and cancer. [ 33,34 ] In addition, metal complexes containing phenanthroline ligands have been shown to interact highly with DNA and induce cytotoxicity in various cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox inertness potential, low toxicity, excellent biocompatibility, strengthening of the immune system, and increased expression of genes are good reasons for the synthesis of zinc‐based metal complexes. [ 8 ] On the other hand, metal complexes containing phenanthroline ligands and their derivatives could be the future drugs on the market, because they have been shown to be active against various pathological conditions including germs, fungal infections, and cancer. [ 33,34 ] In addition, metal complexes containing phenanthroline ligands have been shown to interact highly with DNA and induce cytotoxicity in various cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] Accordingly, Eskiler and Kani confirmed that Zn(II) complex containing bipyridine exhibited undesirable effects on human umbilical vein endothelial cells (HUVECs) and may cause severe complications in patients. [ 8 ] That is why we synthesized a new complex with Phen and folic acid (FA) so that could control the dose of zinc through targeted drug delivery and reduce the risk of carcinogenesis in patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out by Eskiler and Kani demonstrated that Zn(II) complex can significantly suppress the viability of human breast cancer cells of the MCF-7 line by inducing apoptosis through multi-caspase activity in breast cancer cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…In order to solve the shortcomings of the previous generation of platinum complexes, the design strategy of new platinum complexes has been deeply studied. 21 Therefore, it is urgent to develop more targeted antitumor candidates with fewer side effects.…”
Section: Introductionmentioning
confidence: 99%